An Essential Role of the Avidity of T-Cell Receptor in Differentiation of Self-Antigen-reactive CD8+ T Cells. Issue 3 (April 2016) - Kondo, Kenta; Fujiki, Fumihiro; Nakajima, Hiroko; Yatsukawa, Erika; Morimoto, Soyoko; Tatsumi, Naoya; Nishida, Sumiyuki; Nakata, Jun; Oka, Yoshihiro; Tsuboi, Akihiro; Hosen, Naoki; Oji, Yusuke; et al.
Abstract : Many studies demonstrated crucial roles of avidity of T-cell receptor (TCR) in T-cell fate. However, majority of these findings resulted from analysis of non–self-antigen-specific CD8 + T cells, and little is known about roles of TCR avidity in the fate of self-antigen-specific CD8 + T cells. Wilms tumor gene 1 (WT1) protein is a self-antigen most suitable for addressing this issue because WT1 protein is a highly immunogenic, typical self-antigen. Here, we isolated 2 distinct and functional TCRs, TCR1 and TCR2, from murine WT1 peptide (RMFPNAPYL)-specific cytotoxic T lymphocytes (WT1-CTLs) and generated TCR1-retrogenic (Rg) and TCR2-Rg mice under T and B-cell-deficient and -reconstituted conditions. TCR1-transduced CD8 + T (TCR1-T) cells had approximately 2-fold higher avidity to WT1 peptide than TCR2-transduced CD8 + T (TCR2-T) cells. Cytokine production profiles and cell surface phenotypes showed that TCR1-T cells were more differentiated than TCR2-T cells under both conditions. Therefore, TCR1-T cells with TCR avidity higher than that of TCR2-T cells are more differentiated compared with TCR2-T cells. Furthermore, TCR1-T cells that developed under T and B-cell-reconstituted conditions displayed cytotoxicity against endogenously WT1-expressing tumor cells, whereas TCR2 T cells that developed under the same conditions did not. Thus, it was demonstrated, for the first time, that TCR avidity played an essential role in differentiation of self-antigen-reactive T cells, through the success of establishment of two distinct WT1-CTLs with a difference in only TCR avidity under the identical genetic background. Present results should provide us with an insight for elucidation of the differentiation mechanisms of self-antigen-reactive T cells, including tumor antigen–reactive T cells.